Classification of Ionograms Obtained from Vertical Incidence Pulsed Ionospheric Radar (VIPIR)/Dynasonde Ionospheric Radar at Jang Bogo Station, Antarctica - Junho Back; Geonhwa Jee; Hyuck-Jin Kwon; Khan-Hyuk Kim; Changsup Lee; Young-Bae Ham; Nikolay Zabotin (Journal of Astronomy and Space Sciences, 2025)
The electron density profiles produced from the ionospheric sounding system are traditionally estimated by the inversion procedure based on the image analysis of the observed ionograms. Jang Bogo Vertical Incidence Pulsed Ionospheric Radar (VIPIR) with Dynasonde (hereafter, JVD), however, uses the three-dimensional electron density inversion approach named “NeXtYZ” to produce ionospheric density, ion velocity, and tilt of the ionization in the bottomside ionosphere based on the list of detected radio echoes with their physical parameters. Sometimes, the resulting density profiles can be erroneous, not reflecting real ionosphere, probably due to severely disturbed ionosphere in the polar region. In this study, the automatic classification procedure of the estimated electron density profiles is developed to filter out unusable data for the 5-year period from 2017 to 2021. The ionograms are classified into four categories: ‘Unavailable’, ‘Sporadic E’, ‘Needs Reprocessing’, and ‘Available’. It is found that approximately 50% of ionograms are evaluated to be reasonable with proper electron density profiles and about 35% of them tend to be affected by sporadic-E like structures, blocking the F-region ionosphere to be observed. It should be noted that the sporadic-E like structures in the polar ionosphere seems to be main obstacles for the ionospheric sounding observation of the F-region ionosphere. Only less than 10% of ionograms are classified as a reprocessing type which needs to be reprocessed. Finally, no echoes are recognized by Dynasonde analysis for about 5% of ionograms. The reprocessing and/or unavailable types might be associated with auroral precipitations that disturbs the ionosphere in the polar region.